1997
DOI: 10.1016/s1078-5884(97)80084-6
|View full text |Cite
|
Sign up to set email alerts
|

A prospective survey of patients presenting with abdominal aortic aneurysm

Abstract: The presentation of AAA in this study was approximately 15 per 100,000 population. Approximately one-third of patients presenting electively had small AAAs which required surveillance. A further third underwent an operation, the remaining patients being unfit. Approximately one-quarter of patients with a ruptured aneurysm did not undergo an operation. The operative mortality was 37%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…35 Szilagyi et al 36 reported 11% of patients unfit for open repair rupture within one year of presentation, and studies have supported the considerable incidence of death from AAA rupture in high risk cohorts that are treated conservatively. 21, 37, 38 Thus, a significant portion of the AAA population will likely die from rupture if they are excluded from endovascular repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Szilagyi et al 36 reported 11% of patients unfit for open repair rupture within one year of presentation, and studies have supported the considerable incidence of death from AAA rupture in high risk cohorts that are treated conservatively. 21, 37, 38 Thus, a significant portion of the AAA population will likely die from rupture if they are excluded from endovascular repair.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative risk stratification for noncardiac vascular surgery has been investigated by others and validated, using mathematical models to derive scoring systems and predict mortality. 10, 3032, 3537 Analysis of the large Medicare dataset provided sufficient statistical power to accurately identify specific individual criteria predictive of 30-day mortality for EVAR. Our scoring system allows a comparison of the impact of individual factors on mortality, and importantly, a summation of their combined effects.…”
Section: Discussionmentioning
confidence: 99%
“…1 With 60% of patients dying before ever reaching the hospital, those who ''arrive alive'' have a greater than 50% operative mortality. 2,3 This is in contrast to an elective repair mortality rate of 1% to 5%. 1,4 Mortality is directly related to the timeliness of diagnosis before rupture and definitive repair.…”
mentioning
confidence: 88%
“…These observations may not be isolated because others have noted sample populations presenting with AAA in which a substantial proportion did not meet conditions for operations. 3 Although most of the patients with ''true'' AAA did not go to the operating room, the potential end point of operative repair may not be the gold criterion for evaluating the merit of EUS-AA. As contrasted with trauma ultrasound, therapeutic laparotomy may be a more subjective and unrealistic goal regarding the individual patient with AAA.…”
Section: Discussionmentioning
confidence: 99%
“…1 With 60% of patients dying before ever reaching the hospital, those who ''arrive alive'' have a greater than 50% operative mortality. 2,3 This is in contrast to an elective repair mortality rate of 1% to 5%. 1,4 Mortality is directly related to the timeliness of diagnosis before rupture and definitive repair.…”
Section: Prospective Study Of Accuracy and Outcome Of Emergency Ultramentioning
confidence: 90%